Competence assessment of the clinical tutor: a multicentric observational study - La Sala, Rachele; Coppola, Debora; Ruozi, Corrado; Martelli, Michele; Lo Coco, Alessandro; Marchini, Romano; Gotri, Lucia; Pedrazzi, Giuseppe (Acta Biomedica Atenei Parmensis, 2021)
Background and aim of the study: In the international literature there are no validated tools which investigate clinical tutors’ skills. The main objective of the study has been to describe the clinical nurse tutor’s skills, required to properly train nursing students during their educational path. Methods: In this observational study a non-probability sampling has been used. The study was led in two centers: the AOUPR of Parma and the AUSL of Parma, after obtaining the favorable opinion from the Ethics Committee of the Northern Emilia Large Section. The data have been collected by using a structured and self-given survey that investigated three areas. Each item has a 4-point Likert scale, in which 1 indicates "for nothing" and 4 "very much". The data have been analyzed with the statistical software IBM SPSS v.26 ® and with the open-source statistical software Jamovi v.1.6.9 (https://www.jamovi.org.). The number of factors in the original model was reduced using several established research steps and then evaluated for data quality and construct validity using principal component analysis and confimatory factor analysis. Results: Among 397 administered questionnaires, only 300, which were considered valid, have been filled. The psychometric properties of the investigation tool turned out to be good in all the areas analyzed with a Cronbach alpha higher than 0.70. The extensive process resulted in a version with 4 factors. Conclusions: Nurses’ answers have allowed to draw the required profile of the clinical tutors in the different organizational contexts. The results can target possible training proposals to create opportunities for the clinical tutors.